Benefits and harms of using a tourniquet in total knee arthroplasty - Filho, Otoni Lima de Oliveira; Valle, Arthur Lucena; Borba, Pedro Henrique Cirne; Pereira, Rafael Cavalcanti; Fabrício, Maria Clara Fernandes; Confessor, Maine Virgínia Alves (Seven Editora, 2024)
The use of a tourniquet is important to combat bleeding during total knee arthroplasty (TKA). The initial equipment, invented in 1817 by Petit and improved in 1904 by Cushing, consists of a device that compresses blood vessels, controlling the flow of blood to one extremity, while the 1904 technique consists of a pneumatic compression monitored by the microcontroller and the inflatable cuff of the device. DOI:https://doi.org/10.56238/sevened2024.025-029